Uso de óleos funcionais em substituição a antibióticos ionóforos na nutrição de ruminantes: estudo meta-analítico - Gallarreta, Bernardo da Trindade (2020)
In order to evaluate the replacement of the antibiotic monensin by a natural additive capable of modulating rumen fermentation composed of two functional oils (castor oil and cashew nut oil), the present meta-analytical study was conducted. Nine works related to the production of large ruminants were selected, tabulated and meta- analyzed after a systematic review. The statistical program R, version 3.5.2, was used to analyze the variables, selecting the ‘meta’ package, ‘metacont’ function. Eighteen variables were evaluated: dry matter intake (DMI), animal efficiency (AE), milk production (MP), milk production corrected to 3.5% fat (MPC 3.5%), fat content in milk (FM), milk protein content (MP), milk lactose content (MLAC), daily milk fat production (DMFP), daily milk protein production (DMPP), daily milk lactose production (DMLACP), neutral detergent fiber intake (NDFI), neutral detergent fiber digestibility (FDND), acetate: propionate ratio (A:P), average daily gain (ADG), rumen acetate (RA), rumen propionate (RP), rumen butyrate (RB) and animal protein (AP). Milk fat content and daily milk fat production differed (P <0.05) from one additive to the other, the others showed no difference (P> 0.05). The mixture of functional oils can be an alternative to improve the efficiency of the ruminant, and can be used as a substitute for the ionophore monensin antibiotic.